Using the Quadruple Helix Model for evaluation of health science researches: Case study of D8 countries. Issue 4 (17th March 2020) - Moradi, Shima; Dokhani, Firoozeh
Abstract : Purpose: Altmetrics is a complementary method in scientometrics for evaluating the performance of individuals, organizations, institutions and countries in social media. Due to the large volume of data related to the interactions in science, technology and innovation, there is no choice but to develop and implement accurate models for analysis and decision making. The Quadruple Helix Model examines the scientific outcomes in four spaces of innovation, knowledge, consensus and government with a distinctive attention to the "innovation space". In other words, it aims to find the connection between the academic space and other sectors of a society (public, media and government) to see if scientific outputs respond appropriately to their needs. Design/methodology/approach: The present paper studied the impact of health-related researches in D8 countries) including Iran, Turkey, Pakistan, Bangladesh, Indonesia, Malaysia, Egypt and Nigeria) using the Altmetrics scores of their indexed journal in the Web of Science (WOS). The results demonstrated distribution of interactions of the mentioned four spaces in health science researches in terms of social media, geographical distribution and theme for D8 countries. This was conducted using content analysis, scientometric and altmetric indicators in the WOS and Altmetrics.com databases. Findings: In D8 countries, more interaction has taken place in the knowledge and innovation spaces; however, there exist Quadruple imbalances in these countries. Moreover, some interactions have been observed in all social networks, displaying that users consider health topics in D8 countries, and clinical sciences has gotten more interaction in all the four spaces. Originality/value: The application of this model using altmetrics data with current approach has been conducted for the first time.